Preparation and characterization of cobalt based and zinc promoted catalyst fro fisher tropsch synthesis - Nur Hayati, Zulkefli (2011)
The purpose of this research is to compare the characterization of SBA-15 and TiO2 supported cobalt catalyst for Fischer-Tropsch synthesis based on effect of cobalt loading. In order to complete this research, the catalyst must be prepared by incipient wetness impregnation method. The catalysts were prepared with different cobalt loading, which are 5%, 10% and 15% and using zinc as a promoter. To characterize these catalysts, different methods were used. First of all, characterization of SBA-15 and TiO2 were compared by using Fourier Transform Infrared Spectroscopy (FTIR). Then the catalysts were tested using Scanning Electron Microscope (SEM). Through this characterization, the surface of catalysts was compared. The surface structure of Co/SBA-15 is more ordered when compared to Co/TiO2 catalyst. This is compared by the SEM image taken. Therefore, Co/TiO2 is also a good catalyst with advantages when compared to Co/SBA-15 catalyst. The conclusion of this research when comparing the characterization of Co/SBA-15 and TiO2 catalysts, is Co/SBA-15 catalyst is a good catalyst when compared to Co/TiO2 catalyst.